Gotong Royong among the Simbatan Wetan Hamlet Community in Magetan during Bersih Desa Rituals at Petirtaan Dewi Sri - Mahdhalena, Eksanti Yolla; Sukmawan, Sony (Faculty of Humanities, Universitas Jenderal Soedirman, 2025)
This research aims to describe and analyze in depth the culture of gotong-royong contained in the bersih desa rituals at Petirtaan Dewi Sri using folkloric studies. Through descriptive qualitative method, data collection techniques in the form of interviews and documentation and then analyzed by applying the Miles and Huberman interaction analysis model so that the research results obtained that the implementation of bersih desa rituals at Petirtaan Dewi Sri starts from the preparation stage, environmental cleaning, selametan to the core activities. The implementation of this bersih desa rituals is due to the four forms of gotong-royong culture carried out by the people of Simbatan Wetan Hamlet, namely physical, material, thought and immaterial gotong-royong. The attitude of the people of Simbatan Wetan Hamlet who are willing to set aside time, energy and contribute ideas, prayers and materials for the common good shows that the community has a full awareness of respect and concern for each other so as to create harmony between communities and encourage the realization of pluralism.